Síntese de complexos organometálicos de cobalto (II) e ferro (II) contendo ligante isocianeto - Pavan, Jamile Rocha (2008)
In this work there will be presented the preparation of highly colored compounds of the general formula [Co(t-BuNC)nX2], isolated to the low temperature in the reaction of CoX2hydrated (X = Cl, Br and I) with t-BuNC in acetone and under inert atmosphere of argon. The products has been characterized by CHN microanalysis, cobalt analysis by titulation with EDTA, TG/DTG in atmosphere of oxygen, and electrolytic conductivity in acetone. The local symmetry D4h(Eu) has been attributed for the compound with X = I (?(CN) = 2181, 3 cm-1) with based on the spectroscopic analysis in the infrared one. Measure of susceptibility magnetic indicates that the complex is paramagnetic with one unpaired electron. This compound presents a thermal decomposition (TG/DTG) in two stages. The process of decomposition of the products with bromide and chloride was similar to that of an iodide, though his taken place in less temperatures, since they were composed less stable. Finally, the low conductivity in solution proved the nature not eletrolitic of these products.The complex [CoMNT(t-BuNC)2] has been obtained from the equimolar reaction of CoCl2. 2H2O, Na2MNT, and excess of t-BuNC in acetone. The product was identified through elementary analysis (CHN), IR,TG/DTG in atmosphere of oxygen, electrolytic conductivity in acetone and magnetic measure. Two structures are probable: tetrahedral and square planar. The magnetic measure indicated the formation of the square planar structure.This work aims also several?-acids ligands to study the influence of in the chemical stability from the iron. Complexes chelates of formula [Fe(MNT)(LL)(t-BuNC)2] (MNT = S2C2(CN)2; LL = phen or bipi), identified through elementary analysis (CHN), thermogravimetric analysis, infrared spectra and Mössbauer was obtained from the equimolar reaction of FeBr2, Na2MNT, LL and excess of t-BuNC in THF. The infrared spectra in the region of the ?(CN) presented three absorption around 2189, 2130 and 2090 cm-1. The higher frequency is attributed to ?(CN) of the chelate MNT and two lower band are attributed to ?(CN) of the isocyanide. Two structures are probable: cis (C1) and trans (C2v) relative to an isocyanide, which they are indistinguishable for the infrared one because of presenting the same activity for ?(CN). The Mössbauer parameters indicate an xvincrease of the ?-back donation in the atom from iron and an environment octahedral distorted relatively to the FeBr2precursor. The thermogram of the adducts support the results of the elementary analyses and indicate a more thermal stability for the derivate of bipyridine (decomposition to 138.9°C), regarding the derivate o-phenantroline (109.5°C). The synthesis of these complexes was of abridgement importance, because it allowed to correlate data vibration and nuclear property, besides supplying important information on the nature of the iron atom bond.